Triple Aspiration versus Conventional Aspiration Techniques: A Randomized In Vitro Evaluation - Bilgin, Cem; Li, Jiahui; Bayraktar, Esref Alperen; Naylor, Ryan M.; Oliver, Alexander A.; Ueki, Yasuhito; Cortese, Jonathan R.; Rinaldo, Lorenzo; Kadirvel, Ramanathan; Brinjikji, Waleed; Cloft, Harry J.; Kallmes, David F. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: A single-aspiration maneuver using a large-volume syringe is a common and effective technique for aspiration thrombectomy. Multiple aspiration cycles using large aspiration syringes have been proposed as a means to improve the efficacy over single aspiration. In this study, we sought to investigate the efficacy of a “triple aspiration technique” in which a large-volume syringe is cycled 3 times before catheter retraction during aspiration thrombectomy.MATERIALS AND METHODS: A 3D-printed adult vasculature was used as a benchtop thrombectomy platform. Fibrin-rich and red blood cell–rich clots were prepared in centrifuge tubes using human plasma, red blood cells, and calcium chloride. Next, clots were placed in the carotid terminus of the model, and the performances of 3 different aspiration techniques—triple syringe, single syringe, and continuous pump aspiration—were compared in a randomized manner (1:1:1). Outcomes of interest included first-pass efficacy (FPE), complete clot removal (final modified TICI 2c/3), the number of thrombectomy attempts to achieve modified TICI 2c/3, vacuum pressure, and distal embolization. The distal emboli were detected using a 70-μm cell strainer placed at the outflow of the model and quantified using an image-processing algorithm. The vacuum pressures were measured using a pressure transducer.RESULTS: A total of 102 replicates were performed, 34 for each technique. The triple-aspiration technique provided a significantly higher rate of FPE than the syringe and pump aspiration techniques (67.6% versus 41.1%, P = .02). Additionally, the triple-aspiration technique achieved complete clot removal with a significantly lower mean number of thrombectomy attempts compared with single-syringe aspiration (1.2 [SD, 0.5] versus 1.8 [SD, 0.8], P = .005). The triple-aspiration technique generated significantly higher mean vacuum pressure than both the single-syringe and vacuum pump aspiration (28.3 [SD, 0.2] versus 27.2 [SD, 0.3], P = .002 and 26.2 [SD, 0.4], P = .001, respectively). The differences in complete clot removal and distal embolization parameters were not statistically significantly different across the groups.CONCLUSIONS: Our findings suggest that the triple aspiration technique can improve FPE rates and vacuum pressure in aspiration thrombectomy. Further studies are needed to examine the safety and efficacy of triple aspiration in the clinical setting.AcomAanterior communicating arteryFPEfirst-pass efficacyMTmechanical thrombectomymTICImodified TICI scalePcomAposterior communicating arteryRBCred blood cell